1979
DOI: 10.1002/hlca.19790620132
|View full text |Cite
|
Sign up to set email alerts
|

Zur Photochemie von 1H‐ und 2H‐Indazolen in saurer Lösung

Abstract: It is shown that I Hand 2H-indazoles (cf: Scheme2) on protonation ( 0 , l~ H2S04 in water or alcoholic solution) give analogous indazolium ions (see Fig. 1 and 2) which on irradiation undergo heterolytic cleavage of the N(l), N(2) bond whereby aromatic nitrenium ions in the singlet ground state are formed (cf: Scheme 13). If the para position of these nitrenium ions is not occupied by a substituent (e.g. a methyl group) they are readily trapped by nucleophiles present (e.g. water, alcohols, chloride ions) to y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1979
1979
1999
1999

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 61 publications
0
1
0
1
Order By: Relevance
“…A survey of the literature revealed no reliable and practical procedure for 15 although its protected forms have been reported recently as an intermediate for the synthesis of camptothecin analogues . Initially, aminohydroxybenzaldehyde 15 was prepared by photoreaction of indazole; however, the photoreaction was an obvious drawback for the large-scale preparation. From these initial experiments, we concluded that 15 had not been available presumably owing to its lability.…”
Section: Resultsmentioning
confidence: 99%
“…A survey of the literature revealed no reliable and practical procedure for 15 although its protected forms have been reported recently as an intermediate for the synthesis of camptothecin analogues . Initially, aminohydroxybenzaldehyde 15 was prepared by photoreaction of indazole; however, the photoreaction was an obvious drawback for the large-scale preparation. From these initial experiments, we concluded that 15 had not been available presumably owing to its lability.…”
Section: Resultsmentioning
confidence: 99%
“…C 80,82 H 7,64 N 5,75% 2.5. Bestrahlung (5) [lo]. KR.-Destillation bei 1 10-120"/10-3 Torr lieferte 103 mg (6,6%) 5i vom Smp.…”
Section: Experimenteller Teilunclassified